The Relationship Between Physical Activity and Primary Infertility in Iranian Women - Abbas Saremi; Rahmatollah Moradzadeh (Women’s Health Bulletin, 2024)
Background: Inadequate lifestyle choices, such as insufficient physical activity, may be linked to adverse fertility outcomes. Given the profound influence of lifestyle on women’s reproductive health, this study was undertaken to compare the levels of physical activity and body composition among fertile and infertile Iranian women in 2022.Methods: This cross-sectional study encompassed 653 fertile women (mean age: 32.58±5.99 years, mean body mass index (BMI): 25.7±3.64 kg/m²) and infertile women (mean age: 32.59±5.38 years, mean BMI: 26.4±5.6 kg/m²) who sought assistance at infertility centers in six provinces (Guilan, Markazi, Hamedan, Sistan, and Baluchestan, Isfahan, and Khuzestan) during the research period spanning 2021 to 2022. Participants completed questionnaires regarding their lifestyle habits and physical activity levels, body composition was also assessed. Chi-square and multiple logistic regression tests were employed for data analysis.Results: Fertile women exhibited superior physical activity (P=0.04) and a lower BMI (P=0.001) than their infertile counterparts. Women with a high level of physical activity (OR=4.42, P=0.004) were more likely to experience infertility. Inactive women who spent more than 300 minutes per day sitting were 2.07 times more susceptible to fertility complications than their physically active peers (moderate activity) (OR=2.07, P=0.001).Conclusion: Given the simultaneous increase in obesity, inactivity, and infertility among Iranian women, it is imperative to place greater emphasis on lifestyle habits, including appropriate physical activity, to prevent and potentially treat infertility.